Implementation of Character Education in Civic Education Learning at SDN 2 Kalosi, Alla District, Enrekang Regency - Usman, Julianti (Jurnal Keguruan dan Ilmu Pendidikan (JKIP), 2024)
The main issues in this study are how character education is implemented in Civic Education at SDN 2 Kalosi Elementary School, Alla District, Enrekang Regency, and the factors that influence the implementation of character education in Civic Education at SDN 2 Kalosi Elementary School, Alla District, Enrekang Regency. This study is descriptive-qualitative in nature. The data collection techniques used included observation, in-depth interviews, and documentation. The analysis method used consists of three stages, namely data reduction, data presentation, and verification. The results of the study show that the implementation of character education in Civic Education learning is based on the 2013 curriculum, which includes character values ​​in every lesson plan (RPP). Teachers use this plan as a guide in implementing learning and instilling character values ​​in accordance with learning activities. The implementation of character education in Civic Education learning is included in thematic learning so that the instilling of character values ​​is followed by other learning activities. Factors that influence the implementation of character learning include environmental factors, cultural factors, family factors, and instinctive factors. These four factors have different influences on students’ characters.